Need and utilization of primary health care among long-term unemployed Finns - Jan Klavus; Leena Forma; Jussi Partanen; Pekka Rissanen (Journal of Health and Social Sciences)
Introduction: Aim of this paper was to identify the attributes of primary health care utilization among long-term unemployed Finns, and to examine whether access to care and the choice of provider differ with respect to employment status. Methods: Data on primary health care utilization were derived from two sources; a targeted questionnaire about the use of services and quality of life among long-term unemployed individuals, and the Welfare and Services in Finland Survey, covering the general population. A two-part econometric model was applied in order to separate between the probability and level of utilization. The statistical analysis allowed predicting the monetary costs of primary care utilization. In this context, a non-parametric smearing factor was used to adjust for retransformation bias. In addition, a distinction between the level of costs and number of visits was taken to account for the effect of unit cost variation. Results: The analyses indicated that the utilization of primary health care services among the long-term unemployed varied with respect to gender, self-rated health status and economic situation, place of residence, marital status and duration of unemployment. The scope of analysis was shown to be fundamental for the interpretation of the comparative results. Taking into account the provision of occupational care services inverted the positive effect of long-term unemployment on primary care utilization. Further, while the costs of utilization were independent of employment status, long-term unemployment had a distinct reducing effect on the number of medical visits. Discussion and Conclusion: Despite of greater health care needs, the long-term unemployed sought less visits to more costly public primary care services. In order to confront unmet health care needs among the long-term unemployed, public sector interventions should be targeted accordingly, and in particular, involve gender specific social marketing measures.